Herbal Plants: The Role of AhR in Mediating Immunomodulation - Bungsu, Izzah; Kifli, Nurolaini; Ahmad, Siti Rohaiza; Ghani, Hazim; Cunningham, Anne Catherine (Frontiers in Immunology, 2021)
The prevalence of chronic inflammatory diseases including inflammatory bowel disease (IBD), autoimmunity and cancer have increased in recent years. Herbal-based compounds such as flavonoids have been demonstrated to contribute to the modulation of these diseases although understanding their mechanism of action remain limited. Flavonoids are able to interact with cellular immune components in a distinct way and influence immune responses at a molecular level. In this minireview, we highlight recent progress in our understanding of the modulation of immune responses by the aryl hydrocarbon receptor (AhR), a ligand-dependent transcription factor whose activity can be regulated by diverse molecules including flavonoids. We focus on the role of AhR in integrating signals from flavonoids to modulate inflammatory responses using in vitro and experimental animal models. We also summarize the limitations of these studies. Medicinal herbs have been widely used to treat inflammatory disorders and may offer a valuable therapeutic strategy to treat aberrant inflammatory responses by modulation of the AhR pathway.